MORTALITY IN EXPERIMENTAL AND NATURAL INFECTION CAUSED BY HIGHLY PATHOGENIC INFLUENZA VIRUS H5N1 - A. V. Zaykovskaya; S. A. Leonov; Yu. G. Yushkov; I. Y. Rassadkin; A. M. Shestopalov (Acta Biomedica Scientifica, 2012)
In this paper the data for mortality from experimental infections and natural contamination in different species of poultry is presented. Mortality of natural contamination was identified during the epizootic of influenza in the Novosibirsk area in July 2005. We infected domestic geese, ducks and two breeds of chickens with highly pathogenic influenza virus A/goose/Krasnoozerskoye/627/05 (H5N1) for the experiments constructed.